Nutrition and diet profile: Sri Lanka - Koyratty, Nadia; Silva, Renuka; Ranathunga, Thilanka; Olney, Deanna K. (International Food Policy Research Institute, 2024)
• Sri Lanka faces a double burden of malnutrition with the co-existence and persistence of multiple forms of malnutrition, e.g., stunting, wasting, underweight, overweight/ obesity, anemia, and micronutrient deficiences. • Inadequate intake of many micronutrients is common across several population groups in Sri Lanka, indicating low intake of nutrient-dense foods such as F&Vs and animal-source foods. • A diverse diet with adequate intake of nutrient-dense foods should be encouraged to address nutrient gaps among Sri Lankans and reduce the risk of NCDs. • Many government-issued diet- and nutrition-related policies, strategies, and programs have been adopted in Sri Lanka. However, these often do not place enough emphasis on F&Vs. • While national food based dietary guidelines exist, as well as other guidelines and policies, there is uncertainty about the level of public awareness and the population’s adherence to the recommendations. • Evaluations of diet- and nutrition-related interventions are also scarce, indicating a need for rigorous evidence on what works to help guide programs and policies that aim to improve diet and nutrition outcomes among Sri Lankans.